Trans-suppression of host CDH3 and LOXL4 genes during Cryptosporidium parvum infection involves nuclear delivery of parasite Cdg7_FLc_1000 RNA. Issue 6 (May 2018) - Ming, Zhenping; Gong, Ai-Yu; Wang, Yang; Zhang, Xin-Tian; Li, Min; Li, Yao; Pang, Jing; Dong, Stephanie; Strauss-Soukup, Juliane K.; Chen, Xian-Ming
Graphical abstract: Highlights: Cryptosporidium parvum infection causes downregulation of CDH3 and LOXL4 genes in host intestinal epithelial cells. A parasite RNA Cdg7_FLc_1000 is recruited to the promoter regions of both CDH3 and LOXL4 gene loci following infection. Cdg7_FLc_1000 promotes PRDM1/G9a-mediated H3K9 methylation associated with trans-suppression of CDH3, but not LOXL4 . Abstract: Intestinal infection by Cryptosporidium parvum causes significant alterations in the gene expression profile in host epithelial cells. Previous studies demonstrate that a panel of parasite RNA transcripts of low protein-coding potential are delivered into infected host cells and may modulate host gene transcription. Using in vitro models of human intestinal cryptosporidiosis, we report here that trans-suppression of the cadherin 3 ( CDH3 ) and lysyl oxidase like 4 ( LOXL4 ) genes in human intestinal epithelial cells following C. parvum infection involves host delivery of the Cdg7_FLc_1000 RNA, a C. parvum RNA that has been previously demonstrated to be delivered into the nuclei of infected host cells. Downregulation of CDH3 and LOXL4 genes was detected in host epithelial cells following C. parvum infection or in cells expressing the parasite Cdg7_FLc_1000 RNA. Knockdown of Cdg7_FLc_1000 attenuated the trans-suppression of CDH3 and LOXL4 genes in host cells induced by infection. Interestingly, Cdg7_FLc_1000 was detected to be recruited to the promoter regions of both CDH3 and LOXL4 gene loci in host cells following C. parvum infection. Host delivery of Cdg7_FLc_1000 promoted the PH domain zinc finger protein 1 (PRDM1)-mediated H3K9 methylation associated with trans-suppression in the CDH3 gene locus, but not the LOXL4 gene. Therefore, our data suggest that host delivery of Cdg7_FLc_1000 causes CDH3 trans-suppression in human intestinal epithelial cells following C. parvum infection through PRDM1-mediated H3K9 methylation in the CDH3 gene locus, whereas Cdg7_FLc_1000 induces trans-suppression of the host LOXL4 gene through H3K9/H3K27 methylation-independent mechanisms.